Effect of Copper Chemical Form on The Growth of Pseudomonas aeruginosa Isolated from Burned Patients and on Its Cu Uptake (Journal of Basic and Applied Research in Biomedicine, 2022)
The main object of this investigation was to shed light on the information on the level of Cu uptake by Pseudomonas aeruginosa that has been previously isolated from patients using Gram-negative E. aerogenes ans a Gram-positive Bacillus thuringiensis as a control for Cu uptake measurements. Cu uptake data showed that maximum Cu uptake was obtained by the Pseudomonas aeruginosa. The metal uptake was dependent on the type of biosorbent with different accumulation affinities toward the tested chemical form of the copper. Cells harvested at exponential growth phase showed slightly higher Cu uptake than at stationary phase, which reflect that the Cu uptake is metabolism dependent-process. The increasing order of affinity of the cupric chloride and cupric sulphate towards the three genera were almost constant. However, where cupric nitrate was used, the copper uptake behavior in Pseudomonas aeroginosa was not changed from those results with the other two chemical forms, whereas with E.  aerogenes & B. thuringiensis, different Cu uptake behaviors were observed. In B. thuengenesis, the copper uptake rate as a function of initial Cu concentration were shown to increase with increasing the initial concentration of Cu, constantly above 320 ppm as compared with others. In Enterobacter with cupric nitrate, different bahavior was also shown in which the copper uptake decline sharply beyond the 320 ppm. These results reflect that the Cu uptake in P. aeruginosa is with different mechanisms as compared with other tested bacteria.